Design of a decoupled calibration device for six-axis heavy force sensor based on the orthogonal parallel mechanism. Issue 4 (May 2019) - Lin, Sheng; Sun, Liguang
Abstract: Six-axis heavy force sensors are widely used in heavy manipulator, but the development of the six-axis heavy force sensor is seriously restricted by the technology of calibration. In order to reduce the positioning error for movement of the sensor or the force source, we employ an orthogonal parallel mechanism as the loading part of the calibration device for six-axis heavy force sensor. The decoupling character is deduced by the force mapping matrix. The calibration device is designed including force source, frame and fixture. The loading mode of the six-axis heavy force is described. The pose error of the calibration device is analyzed. The calibration device can apply the six-axis heavy force simultaneously without moving the sensor or force source.